Study on the causes of growth differences in three conifers after the rainy season in the Xiong’an New Area - Ran, Xin; Qiao, Shenqi; Zhang, Yu; Gao, Xiaokuan; Du, Yuewei; Liu, Bingxiang; Ma, Changming; Mu, Hongxiang (Frontiers in Plant Science, 2023)
Background: The implementation of the Millennium Forestry Plan was accompanied by growth discomfort exhibiting varying degrees of symptoms in some coniferous forests after the rainy season. This study involved analyzing the external morphology of the plants, assessing leaf pigment content, measuring the root morphological index and root vigor, as well as respiratory characteristics, to evaluate the growth attributes of their root systems in a high soil moisture environment. Methods: In the "Millennium Forest" area of Xiong'an New Area, we selected three coniferous trees and set up three standard sample plots for each conifer. Results: (1) The growth of the three conifers displayed discernible differences in external morphology. Moreover, a decrease in growth condition corresponded to a reduction in crown size, ground diameter, diameter at breast height, leaf length, and new growths. (2) The root biomass, length, surface area, and root volume of conifers growing N class were significantly reduced than those of L class conifers. Conifers with a higher proportion of root systems in the 40-60 cm soil layer experienced more severe stress. (3) The significant decline in root respiration and vigor among all three conifer growth classes (M and N) suggested that the root system was undergoing anoxic stress, particularly at a soil depth of 40-60 cm where root respiration and vigor were notably reduced. (4) The persistent anoxic stress created by long-term exposure to high soil moisture content primarily impacted P. armandii to a greater extent than P. tabuliformis and P. bungeana. Additionally, the transporting and absorbing root ratios varied among conifers with differing growth conditions. The long-term high moisture environment also caused partial death of absorbing roots, which played a key role in the observed differences in growth. (5) Plants with more root distribution in the deeper soil layers grow worse than those distributed in the top soil layers. Soil water content is related to aeration, root distribution, growth and growth of above-ground parts. The variability of root distribution and growth led to the differentiation of the growth of the above-ground part of the plant in terms of external morphology, which inhibited the overall plant growth.